Service user involvement in preregistration general nurse education: a systematic review. Issue 1 (30th October 2015) - Scammell, Janet; Heaslip, Vanessa; Crowley, Emma
Abstract : Aims and objectives: A systematic review of published studies on service user involvement in undergraduate, preregistration general nursing education (excluding mental health‐specific programmes). The objective is to examine how students are exposed to engagement with service users. Background: The requirement of service user involvement in all nurse education is policy expectation of health professional education providers, in response to the increased public and political expectations. Previous literature reviews have focused solely on mental health. Design: Systematic review using the Preferred Reporting Items for Systematic reviews and Meta‐Analyses guidelines; timeframe 1997–2014; published in English. Methods: Search of CINAHL, Cochrane Review, Education Research Complete, Internurse, MEDLINE, PsychINFO, Scopus, SocINDEX and Web of Science yielded 229 citations; 11 studies met the review eligibility criteria. Results: Seven studies used qualitative methodology, two quantitative and two mixed methods. Studies from the United Kingdom dominated ( n  = 9), the remainder from South Africa and Turkey. The results are described using four themes: benefits and limitations of service user involvement; nursing student selection; education delivery; practice‐based learning and assessment. Most studies were small scale; nine had less than 30 participants. Overall the evidence suggests that student, lecturers and service users valued service user involvement in nurse education, to provide an authentic insight into the illness experience. Logistical considerations around support and student cohort size emerged. Conclusions: This is the first systematic review to focus on service user involvement in general nurse education. It reveals that service user involvement commenced later and is more limited in general programmes as compared to equivalent mental health education provision. Most of the evidence focuses on perceptions of the value of involvement. Further research is required to more clearly establish impact on learning and clinical practice. Relevance to clinical practice: Service user involvement in nurse education is valued by stakeholders but preparation and support for those involved, including mentors is underestimated.